Australia’s university Generation Z and its concerns about climate change - Bardales Salguero, Rodrigo; Bogueva, Diana; Marinova, Dora (2024)
Despite scientific evidence about the imminent threat of climate change, people and governments around the world are slow in taking sufficient action. Against these bleak outlooks, Generation Z (Gen Z) born 1995–2010 will inherit the consequences of prolonged inaction. This research delves into the climate change concerns of Australia’s university Gen Z. A representative survey of 446 Australian university students conducted between September 2021 and April 2022 revealed that climate change is the top environmental concern for Gen Z with 81% of these young people being significantly concerned and many experiencing serious climate anxiety. Despite this pervasive concern, 65% of Australia’s university Gen Z is not engaged in traditional climate activism; however, these young people are using technology to voice their concerns. As the future decision-makers of the world, it is crucial for Gen Z to accelerate climate action in all of its forms, including engaging with scientific knowledge and other generations to shape policies and safeguard a liveable planet for all.